2021
DOI: 10.1016/j.heliyon.2021.e06143
|View full text |Cite
|
Sign up to set email alerts
|

Entropy generation in nanofluid flow due to double diffusive MHD mixed convection

Abstract: Lid driven trapezoidal enclosure Low aspect ratio Double diffusive nanofluid flow This work is concerned with the numerical study of laminar, steady MHD mixed convection flow, and entropy generation analysis of 2 3-water nanofluid flowing in a lid-driven trapezoidal enclosure. The aspect ratio of the cavity is taken very small. The cavity is differentially heated to study the fluid flow, heat, and mass transfer rate. The adiabatic upper wall of the enclosure is allowed to move with a constant velocity along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Hirpo 18 analysed the effects of Richradson number on Casson fluid, the Nusselt number increases in a differentially warmed lowest wavy fence. Mondal et al 19 analysed the effects of Richordson number on nanofluid flow, heat and mass transfer increases due to both natural and forced convection and observed that mixed convection phenomenon is more effective than that of natural convection.…”
Section: Introductionmentioning
confidence: 99%
“…Hirpo 18 analysed the effects of Richradson number on Casson fluid, the Nusselt number increases in a differentially warmed lowest wavy fence. Mondal et al 19 analysed the effects of Richordson number on nanofluid flow, heat and mass transfer increases due to both natural and forced convection and observed that mixed convection phenomenon is more effective than that of natural convection.…”
Section: Introductionmentioning
confidence: 99%
“…Chamkha et al 38 said that the reduction in entropy production is caused by the increment in nanoparticles. Mondal et al 39 studied the entropy generation in MHD alumina-water nanofluid numerically. The considered steady, laminar fluid flow was observed through a trapezoidal enclosure and results clearly state that Sherwood and Nusselt number decrease for nanoparticle volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Mondal et al 33 explored the entropy generation (EG) study due to MHD, double‐diffusive mixed convection (DDMC) inside a trapezoidal cavity. One of the walls of the cavity is subjected to linear heating and concentration condition.…”
Section: Introductionmentioning
confidence: 99%